Describing pre‐appointment written materials as an intervention in the context of children's NHS therapy services: A national survey - Samantha Armitage; Elaine McColl; Niina Kolehmainen; Tim Rapley (Wiley, 2021)
Abstract Context Pre‐appointment written materials, including letters and leaflets, are commonly used by healthcare organisations to deliver professional‐patient interactions. The written materials potentially change patients' knowledge and behaviour as part of a healthcare intervention but have received little investigation. Objective To describe the content of pre‐appointment written materials through a behaviour change intervention perspective. Design Mixed methods study with an online questionnaire about pre‐appointment written materials and an analysis of actual materials. Questionnaire data were analysed descriptively and pre‐appointment materials by qualitative framework analysis. Setting and participants Children's community/outpatient occupational therapy, physiotherapy and/or speech and language therapy services across the UK. Service managers/clinical leads provided data. Intervention Pre‐appointment written materials. Results Questionnaire responses were received from n = 110 managers/clinical leads from n = 58 NHS organisations. Written materials (n = 64) were received from n = 24 organisations. Current materials are used by therapy services as a conduit to convey the therapy service's expectations related to: accessing the service, decision‐making about care and help‐giving. The materials enrol the parent and child to the therapy services' expectations by behaviour change techniques. The materials configure the parent/child expectations, knowledge and behaviour towards the therapy services' operational procedures. Conclusion Pre‐appointment written materials configure patients to organisations' operational procedures. The written materials currently lack support for parent/child empowerment, shared decision‐making and self‐management to improve health. Patient Contribution Four parents of children accessing therapy services were involved in the study. The parents shared their experiences to highlight the importance of the topic and contributed to the final research design and methods.